Copper-induced reduction in myocardial fibrosis is associated with increased matrix metalloproteins in a rat model of cardiac hypertrophy. Issue 1 (5th January 2018) - Liu, Yinjie; Xiao, Ying; Liu, Jiaming; Feng, Li; Kang, Y. James
Abstract : AAC induces Cu loss from the heart and depressed MMP-2 in combination with increased TIMPs, leading to increased collagen deposition. TETA replenishes Cu in the heart, increases MMP-2, and decreases TIMP-1 and -2, collectively resulting in reduction in cardiac fibrosis. Abstract : Trientine (TETA), a copper (Cu) chelator, is capable of replenishing Cu in the heart, and Cu repletion reduces cardiac fibrosis in a rodent model of cardiac hypertrophy. This study was undertaken to explore possible mechanisms by which Cu repletion diminishes cardiac fibrosis. Adult male Sprague-Dawley rats were subjected to ascending aortic constriction to induce cardiac hypertrophy. Four months after the operation, cardiac hypertrophy along with fibrosis was fully developed. TETA treatment was then followed at a dose of 21.9 mg kg −1, twice a day, administered orally for six weeks. At the end of the treatment, the hearts were harvested and all of the tissue samples were subjected to qRT-PCR, western blot, Sirius red staining, hydroxyproline assay, and immunostaining analyses. TETA treatment significantly increased the content of Cu in the hypertrophied myocardium, decreased type III collagen deposition and reduced cardiac fibrosis. On the other hand, this treatment did not alter the increase in fibroblasts induced by pressure overload, but significantly increased matrix metalloproteinase-2 (MMP-2), which is the enzyme mainly responsible for degradation of collagens in the heart. In addition, the mRNA and protein levels of tissue inhibitors of matrix metalloproteinase-1 and -2 (TIMP-1 and TIMP-2) were both remarkably increased in the hypertrophic myocardium, and normalized after TETA treatment. The data thus demonstrated that the reduction in cardiac fibrosis by TETA-induced Cu repletion is associated at least in part with an enhanced MMP-2 activity, leading to collagen degradation.